Flow Diverter in Unruptured Intracranial Vertebral Artery Dissecting Aneurysm - Oh, Han San; Bae, Jin Woo; Hong, Chang-eui; Kim, Kang Min; Yoo, Dong Hyun; Kang, Hyun-Seung; Cho, Young Dae (Frontiers in Neurology, 2022)
Objective: Intracranial vertebral artery dissecting aneurysm (VADA) may present as aneurysmal dilation alone, dilation with coexisting stenosis, or, in some cases, as a recurrent aneurysm after previous reconstructive treatment. To date, the clinical utility of flow diverters in VADA has not been examined according to these various circumstances. The aim of our study was to report the safety and efficacy of flow diverters in treatment of various manifestations of intracranial VADA. Methods: Total 26 patients and 27 VADAs treated with flow diverting stents from November 2014 to September 2021 were included. Medical records and radiologic data were analyzed to assess safety and efficacy of flow diverting stents. Results: Twelve cases (44.4%) presented with aneurysmal dilation only, 7 (26.0%) with aneurysmal dilation and one or more associated stenotic lesions, and 8 (29.6%) as recurrence after previous treatment, including stent-assisted coil embolization (n=5), single stent only (n=1), and coil embolization without stent (n=2). Among 27 lesions, 25 were treated with single flow diverters; additional flow diverting stents were required in 2 cases because of incomplete coverage of the aneurysm neck. There was one instance of incomplete expansion of the flow diverter. All cases showed contrast stagnation in the aneurysmal sac immediately after deployment of the flow diverting stent, and during a mean follow-up period of 18.6 months (range 6 to 60), the overall complete occlusion rate was 55.6%, with complete occlusion of 83.3% of aneurysmal dilation only lesions, 42.9% of aneurysms with stenosis, and 25% of recurrent aneurysm. Two patients (7.7%) had delayed ischemic complications. Conclusion: Flow diverters have proven safe and effective in unruptured VADA. However, the complete occlusion rate with the flow diverter is relatively lower in VADA with stenosis or with previous stent placement than in dilation only lesions. Further study with a larger cohort would be needed to confirm these results.